Neurodevelopmental Disabilities in Children With Intermediate and Premutation Range Fragile X Cytosine-Guanine-Guanine Expansions. (March 2014) - Renda, Meredith M.; Voigt, Robert G.; Babovic-Vuksanovic, Dusica; Highsmith, W. Edward; Vinson, Sherry S.; Sadowski, Christine M.; Hagerman, Randi J.
To determine the range of neurodevelopmental diagnoses associated with intermediate (45-54 repeats) and premutation (55-200 repeats) range cytosine-guanine-guanine fragile X expansions, the medical records of children with intermediate or premutation range expansions were retrospectively reviewed, and all neurodevelopmental diagnoses were abstracted. Twenty-nine children (9 female, 20 male; age, 13 months to 17 years) with intermediate (n = 25) or premutation (n = 4) range expansions were identified with neurodevelopmental diagnoses, including global developmental delay/intellectual disability (n = 15), language and learning disorders (n = 9), attention-deficit hyperactivity disorder (n = 5), epilepsy (n = 5), and motor disorders (n = 12), including 2 boys younger than 4 years of age with tremor and ataxia. Thus, children with intermediate or premutation range fragile X cytosine-guanine-guanine expansions may be more susceptible than children without such expansions to other processes, both genetic and environmental, that contribute to neurodevelopmental disability.